Drug resistance pattern of Mycobacteria isolated from smear positive cases of pulmonary tuberculosis in eastern part of Nepal - Pradhan, Prasil; Poudyal, Nimesh; Gurung, Rajendra; Acharya, Anju; Bhattacharya, Shyamal Kumar (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: The emergence of drug resistance in tuberculosis has become a major challenge for effective control of tuberculosis. This study was done with an aim to determine the drug resistance pattern of mycobacteria isolated from pulmonary tuberculosis. Methods: Sputum samples were collected from patients attending B.P. Koirala Institute of Health Sciences, Dharan during 1st June 2006 to 30th May 2007. The smear positive samples were cultured on Lowenstein Jensen medium and drug sensitivity was performed by proportion method. Results: Among 202 Mycobacterial isolates, 96 (47.52%) were sensitive to all four drugs, 50 (24.75%) were resistant to single drug and 15 (7.42%) were MDR strains. Higher rate of MDR was seen in previously treated cases (15.51%) than in new cases (4.6%). Conclusion: This study reflects a high burden of drug resistant tuberculosis in the eastern part of Nepal.